Pengembangan Media Kartu Kamal dalam Penguasaan Kosakata Bahasa Arab - M. Syamsul Ma'arif (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2019)
Vocabulary is one element of language that must be mastered by learners in mastering a particular language including Arabic. Learning Arabic vocabulary requires its own strategies so that the learning will not be boring, one of them is a card games. This study aims to develop Arabic vocabulary learning media in the form of cards named "kamal" as well as to determine their effectiveness. The research design uses Research and Devolopment (R n D) method. Based on the results of the study, it was shown that the kamal card was effectively used as an alternative to the Arabic vocabulary learning media seen from the differences in Student's pre-test and post-test scores. The results of the t-test are obtained t ^ (count)> t ^ table. In the Class "B" series 1 and series 2 t ^ (count) it is 5.390 and 6.890, while the class "D" series 1 and series 2 t ^ (count) are 9.335 and 9.054 with coefficients (dk = 6) then t ^ table between the two classes are the same (2,466).